61.3k views
3 votes
Pls answer me this all question correctly step by step​

Pls answer me this all question correctly step by step​-example-1
User Beau Trepp
by
4.9k points

1 Answer

1 vote

Answer:

A,48

B,6039

Step-by-step explanation:

A,,((90-(13+15))÷2+17 the - symbol multiply the bracket

first do the bracket

((90-13-15)÷2+17

((62)÷2)+17

(31)+17=======48

B,,first let us do the bracket

(5600-110÷10) divided

(5600-11)

(5589)

(5589)+10×45

(5589)+450 === 6039

User Mediarts
by
5.1k points